Swallowing outcomes in dysphagia intervention in parkinson's disease: A scoping review - Walshe, Margaret; Hirschwald, Julia Antonia (My University, 2023)
Objectives: To identify all outcomes, their definitions, outcome measurement instruments (OMIs), timepoints and frequency of measurement applied in clinical trials in oropharyngeal dysphagia (OD) interventions in Parkinson's disease (PD). This scoping review is the first stage of a larger project establishing a core outcome set for dysphagia interventions in Parkinson's disease (COS-DIP). Design: Scoping review. Methods: Six electronic databases and one trial registry were searched without language restrictions until March 2022. Bibliography lists of included studies were also reviewed. Study screening and data extraction were conducted independently by two reviewers using Covidence. The scoping review protocol is registered and published (http://hdl.handle.net/2262/97652). Results: 19 studies with 134 outcomes were included. Trial outcomes were mapped to a recommended taxonomy for COSs and merged. 39 outcomes were identified. The most frequently measured were general swallowing-related outcomes, global quality-of-life outcomes and swallowing-related perceived health status outcomes. The applied outcomes, their definitions, OMIs, timepoints and frequency of measurement showed a high variability across all studies. Conclusions: The high variability of outcomes emphasises the need for an agreed standardised COS. This will inform clinical trial design in OD in PD, increase the quality of OD trials in PD and facilitate synthesising and comparing study results to reach conclusion on the safety and effectiveness of OD interventions in PD. It will not prevent or restrict researchers from examining other outcomes. Trial registration number: The COS-DIP study, including the scoping review, was registered prospectively with the Core Outcome Measures in Effectiveness Trials Database on 24 September 2021 (www.comet-initiative.org, registration number: 1942).
PUBLISHED
Keywords: Behavioral medicine; Movement disorders; Neurology; Ageing; Dysphagia; Evidence based practice; PARKINSON'S DISEASE; Age-related disability; Chronic Health Condition; Health